KONTRIBUSI KEPEMIMPINAN TRANSFORMASIONAL DALAM MENINGKATKAN MOTIVASI DAN KINERJA GURU DI TK IT ALHASANAH - Nurhidayat, Eka Finasie (Jurnal Inovasi dan Teknologi Pendidikan, 2026)
This study aims to determine the contribution of transformational leadership of school principals in improving teacher motivation and performance at Alhasanah IT Kindergarten and its impact on student learning achievement. The background of this research is based on the importance of the role of leadership in forming a professional and inspiring work culture, especially at the level of early childhood education. Transformational leadership is considered to be able to encourage teachers to develop personally and professionally, through an approach that emphasizes example, motivation, intellectual stimulation, and individual attention. This study uses a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, documentation, and questionnaires. The subjects of the study include the principal and teachers of Alhasanah IT Kindergarten. The results of the study show that school principals have implemented various forms of transformational leadership work, such as being spiritual and professional role models, creating innovative programs such as "Guru Berkarya," providing personal guidance, and involving teachers in decision-making. This has a positive impact on increasing teachers' work motivation and their professional performance in planning, implementing, and evaluating learning. Furthermore, increasing teacher motivation and performance contributes significantly to the achievement of children's learning development, especially in cognitive, social-emotional, and spiritual aspects. This